The Physiology of Intrapartum Fetal Compromise at Term. Issue 4 (December 2020) - Turner, J.M.; Mitchell, M.D.; Kumar, S.S.
Abstract : ( Am J Obstet Gynecol . 2020;222:17–26) Nearly a quarter (23%) of neonatal deaths are estimated to be caused by intrapartum complications. Perinatal hypoxia is a major cause of stillbirth, hypoxic ischemic encephalopathy, and cerebral palsy. Three quarters of cases of severe fetal hypoxia are caused by uterine contractions, which reduce uteroplacental perfusion by as much as 60%. While most fetuses can tolerate some reduction of placental perfusion, some cannot. This paper reviewed the physiology of placental development, mechanisms by which intrapartum hypoxia at term manifests in fetuses, and methods of identifying at-risk fetuses.